The link between the gender role self-concept and psychobiological stress in everyday life: an ecological momentary assessment study - Stoffel, Martin; Zintel, Stephanie; Schmidt, Laura; Neubauer, Andreas B.; Sieverding, Monika; Ditzen, Beate (Scientific reports, 2026)
This study examined how trait and state aspects of the gender role self-concept (GSC), beyond biological sex assigned at birth, are associated with psychobiological stress in daily life. We hypothesized that higher agency (self-assertive traits, historically associated with male gender stereotypes) would relate to lower subjective stress and stressor exposure, whereas higher communion (interpersonally oriented traits, historically associated with female gender stereotypes) would show the opposite pattern. Associations with salivary cortisol (sCort) were also investigated. Eighty-two healthy adults (20-65 years; M = 40.0, SD = 12.6; 47.6% female) completed ecological momentary assessments over five consecutive workdays, with seven daily prompts. GSC was measured using the Bem Sex Role Inventory, with trait GSC assessed at baseline and state GSC four times per day. Psychobiological stress was captured via self-reports and sCort. Multilevel models tested associations of trait and state GSC with stress-related outcomes. State agency was negatively associated with subjective stress and stressor exposure, while state communion showed inverse associations with these parameters. Higher trait communion predicted higher sCort. Findings highlight the importance of distinguishing trait and state GSC. Beyond biological sex, GSC explained within- and between-person variation in psychobiological stress, underscoring its relevance for stress research in everyday life.
Gesehen am 12.02.2026